Blood lactate accumulation during open water swimming events in relation to gender. A pilot stydy - Rozi, G.; Thanopoulos, V.; Dopsaj, M.; Lampadari, V.; Okicic, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Open Water Swimming is challenging and special, compared to other endurance sports. Maglischo (2003) states that lactic acid levels in the muscle ranges between 1.0-2.0 mmol/L at rest and between 25-30 mmol/L during maximum effort lasting 1 minute or more. Lactic acid levels of long distance swimmers are usually in the lower part of this range. Lactate accumulation depends on swimming intensity, duration, frequency, the range of oxygen uptake and the muscle fiber type (Maglischo, 2003). The aim of the present study was to identify differences in lactate accumulation in the blood during a 5000m Open Water Swimming effort, between male and female swimmers. Methods: The sample consisted of 5 male, aged 17.5±1.0 years and 6 female, aged 16.4±0.6 years. Lactate accumulation was measured in the 3rd and 10th minute of passive recovery and was analyzed with the portable analyzer Scout Lactate Germany. Heart rate was measured with a Polar device and performance time with a handheld stopwatch Seiko Water Resistant 10bar S140. The research was conducted during a Greek National Open Water Championship, held in June. Results: Analysis of variance showed no statistically significant differences between the two genders for all measured variables. This may be due to the small sample as well as the fact that some of the participants were competing for the first time. Discussion: What should be noted is that there were no particular differences in the blood lactate values between the two genders at 5000m. This finding leads to the conclusion that the energy production mechanism might be similar in both genders. Future studies should focus on larger sample in order to achieve more accurate results.